2020
DOI: 10.21873/anticanres.14304
|View full text |Cite
|
Sign up to set email alerts
|

KHYG-1 Cells With EGFRvIII-specific CAR Induced a Pseudoprogression-like Feature in Subcutaneous Tumours Derived from Glioblastoma-like Cells

Abstract: Background/Aim: We previously established a novel type of epidermal growth factor receptor variant III (EGFRvIII)-specific chimeric antigen receptor (CAR)expressing natural killer (NK) cell line, designated EvCAR-KHYG-1, which inhibited the growth of glioblastoma (GBM) cells in vitro via apoptosis. Materials and Methods: We investigated the cytokine-producing effect of EvCAR-KHYG-1 cells on GBM-like cell lines and their antitumour effect using in vivo xenograft assays. Results: EvCAR-KHYG-1 cells produced inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The in vivo xenograft assay was performed as described previously [ 50 , 51 ]. Briefly, nonobese diabetes (NOD)/severe combined immunodeficiency (SCID)/γcnull (NOG) mice were purchased from the Central Institute for Experimental Animals (Kanagawa, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The in vivo xenograft assay was performed as described previously [ 50 , 51 ]. Briefly, nonobese diabetes (NOD)/severe combined immunodeficiency (SCID)/γcnull (NOG) mice were purchased from the Central Institute for Experimental Animals (Kanagawa, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the nature of the assessed CAR constructs, it was shown that 2 nd generation anti-CD19 CAR-NK cells containing CD3ζ and CD28 costimulatory domains outperformed 1 st generation CARs, whereas 2 nd and 3 rd generation CAR constructs did not seem to confer substantial differences in NK cell functionality ( 215 , 217 ). Investigations on the optimal NK cell source were also conducted, where it was suggested that primary NK sources might be a better option than antiCD19 CAR-NK-92 cells ( 218 , 219 ). In a comparison of CAR PB-NK versus CAR UCB-NK expressing the same antiCD19 CAR construct, it was shown that the former was better in eliminating CD19+ target cells in an effector to target ratio of 1:1 ( 46 ).…”
Section: Car-nk Cells In Preclinical Cancer Researchmentioning
confidence: 99%
“…Murakami et al (2018) [ 241 ] evaluated the engineering of the KHYG-1 NK cell line with an EGFRvIII-specific CAR, and observed the induction of a strong and significant inhibition of EGFRvIII-expressing U87MG GBM cell line growth, through the triggering of apoptosis. A further study by the same group was conducted in 2020 [ 248 ], showing the in vitro secretion of RANTES and—when recognition of U87MG EGFRVIII + tumor cells by CAR-NK cells occurred—a significant secretion of TNF-α, IFN-γ, IL-2, and IL-6 cytokines. However, the treatment of immunodeficient mice bearing the specific target cell apparently failed to control tumor progression, and resulted in greater tumor occupancy, in comparison to PBS-treated mice.…”
Section: Nk-cell-based Immunotherapymentioning
confidence: 99%